Characteristics of Bike taxis in African rural society - (:unkn) unknown (My University, 2020)
This research was conducted during my sabbatical leave from April till September 2019 thanks to the Fondation France-Japon (FFJ) de l’EHESS which accepted me as a visiting researcher. My research, which has exposed that the issue of Bike taxis in rural African cities to be one of the most important determinants of regional socioeconomics, was supported by JSPS KAKENHI Grant Number JP18K11806.
Keywords: African Research